2014
DOI: 10.1371/journal.pone.0089735
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Agonist Augments Virus-Like Particle-Mediated Protection from Ebola Virus with Transient Immune Activation

Abstract: Identifying safe and effective adjuvants is critical for the advanced development of protein-based vaccines. Pattern recognition receptor (PRR) agonists are increasingly being explored as potential adjuvants, but there is concern that the efficacy of these molecules may be dependent on potentially dangerous levels of non-specific immune activation. The filovirus virus-like particle (VLP) vaccine protects mice, guinea pigs, and nonhuman primates from viral challenge. In this study, we explored the impact of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Mice immunized with 40 μg of VEEV-GP MDNP exhibited robust GP-specific T-cell responses 9 d after immunization, as determined by IFN-γ and IL-2 expression by CD8 + and CD4 + splenocytes in response to ex vivo treatment with the EBOV GP-derived WE15 peptide (71) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mice immunized with 40 μg of VEEV-GP MDNP exhibited robust GP-specific T-cell responses 9 d after immunization, as determined by IFN-γ and IL-2 expression by CD8 + and CD4 + splenocytes in response to ex vivo treatment with the EBOV GP-derived WE15 peptide (71) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 98%
“…Splenocytes were isolated from mice 9 d after immunization with 40 μg MDNP and cultured in growth medium [all components were from Life Technologies unless otherwise indicated: RPMI 1620 with GlutaMAX supplemented with 8% FBS, 1 mM nonessential amino acids, 1 mM sodium pyruvate, 10 mM Hepes, 50 μM 2-mercaptoethanol (Sigma), and penicillin/streptomycin]. Cytokine expression in response to stimulation with the immunodominant H-2K b -restricted MHC class I OVAderived peptide SIINFEKL (InvivoGen) or EBOV GP-derived WE15 peptide (WIPYFGPAAEGIYTE) was assayed by intracellular cytokine staining and FACS analysis essentially as described previously (71). Briefly, 1 × 10 7 splenocytes per milliliter were cultured in the presence of IL-2 (10 U/mL), anti-CD28 + antiCD49d (0.5 μg/mL each; BioLegend), and Brefeldin A (2 μg/mL final; Sigma) with or without 2 μg/mL peptide.…”
Section: Methodsmentioning
confidence: 99%
“…TLRs have been implicated in protection against VSV in both in vivo knockout studies (10) and cell culture of dendritic cells (11) and macrophages (12). The TLRs found to be upregulated (TLR1, TLR6, and TLR10) at D0 have not been reported in the context of VSV, but our data suggest that TLR signaling participates in the immunogenicity of VSV⌬G/EBOVgp, as it has in other vaccines (13). At D4 and D7, the response to challenge after immunization also included interferon signaling (upregulation of alpha/beta interferon receptor ical processes that are activated at different time points, we used IPA to carry out an enrichment analysis of the pool of 502 DE genes in manually curated biological networks (14).…”
mentioning
confidence: 53%
“…In the context of VLP vaccinology, Poly I:C has been shown to enhance the protective ability of a VLP-based vaccine against a lethal challenge in a mouse model using a mouse-adapted flu virus [84]. In addition, a VLP-based vaccine for Ebola virus was more efficacious in mice and guinea pigs when adjuvanted with Poly ICLC adjuvant (Hiltonol, Oncovir Inc.) which is a stable combination of Poly IC and Poly lysine [85]. The authors have reported that Poly ICLC boosted antigen-specific immunity mediated by poly-functional CD4+ and CD8+ T cell and antibody responses.…”
Section: Classes Of Adjuvants Tested For Vlp-based Vaccinesmentioning
confidence: 99%